THE INFLUENCE OF MOTIVATION, DISCIPLINE AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS A MODERATION VARIABLE (A Case Study of Asn in Yogyakarta Province) - Lilis Endang Wijayanti; Fran Sayekti; Reschiwati; Dyah Pratita (Dinasti International Journal of Education Management And Social Science, 2020)
The aim of this study is analyzed the factors which influence the performance of the state civil servants (ASN / PNS) who work in the Regional Asset and Financial Management Agency in the Special Region of Yogyakarta. The object of this study are ASN because their performance was assumed not clearly detected. In this study their performance will be linked to work environment, motivation, discipline and work experience. The ASN who have long work experience, high motivation and high discipline resulted good performance. The study uses a moderation variable testing model. The Work Environment as a moderating variable that moderates the effect of the independent variable (motivation, discipline and work experience) on the dependent variable (performance). Work Environment is a working condition and facility faced by ASN. If the work environment is comfortable, ASN will be motivated to work well, so that performance is also high. Experienced ASNs tend to learn a lot from their experience so that their performance is higher. If the ASN is experienced and in a comfortable work environment, the performance will be higher. Likewise, if the ASN has a high level of motivation and discipline and is in a comfortable work environment, the performance will be even higher. The study was conducted by distributing questionnaires to ASN in the area of the Regional Financial and Asset Management Agency in all districts and cities of Wilayah DIY. Data obtained using multiple regression. The results of the data analysis show that the work environment has an effect on ASN performance. The work environment variable also moderates the relationship between work experience and performance.